Local radiation therapy before and during induction delays stem cell mobilization and collection in multiple myeloma patients - Sauer, Sandra; Erdmann, Katharina; Jensen, Alexandra; Wennmann, Markus; Pavel, Petra; Jordan, Karin; Schmitt, Anita; Kriegsmann, Mark; Wuchter, Patrick; Goldschmidt, Hartmut; Müller-Tidow, Carsten; Kriegsmann, Katharina (Transplantation and cellular therapy, 2021)
In multiple myeloma, local radiation therapy (RT) of osseous lesions before peripheral blood stem cell (PBSC) mobilization is assumed to impair the PBSC mobilization and collection. However, the results of previously published studies are inconsistent and do not evaluate detailed metrics of RT and PBSC outcome parameters. In total, 352 patients undergoing PBSC mobilizations and RT in first-line treatment were evaluated. Patients were grouped into RT (n = 283) and no RT (n = 69) before PBSC mobilization. Except for the International Staging System score, both groups were homogeneous regarding the first diagnosis characteristics, first-line treatments, and response parameters. RT metrics (RT yes versus no, volume of irradiated hematopoietic bone marrow [BM], biologically equivalent doses in 2 Gy fractions [EQD2]) were analyzed for the following PBSC outcome parameters: achievement of the PBSC collection goal, CD34+ cell collection yield, duration of the mobilization phase, and number of leukapheresis (LP) sessions to reach the collection goal. No statistically significant differences in the percentage of collection failures to reach at least 3 sufficient PBSC transplants were identified comparing patients with (n = 32 [11%]) and without RT (n = 4 [6%]) before PBSC mobilization (P = .265). However, patients with RT before PBSC mobilization showed a significant prolongation of the PBSC mobilization (median 1 day, P =.026) and required a higher number of LP sessions to reach the collection goal (median 1 LP, P < .001) compared with patients who received RT after PBSC mobilization. Moreover, patients with RT before PBSC mobilization reached a significantly lower CD34+ cell collection result (mean 8.94 versus 9.81 × 106/kg body weight [bw], P = .002). No correlation was identified between the overall CD34+ cell yield and the volume of irradiated hematopoietic BM or EQD2, respectively. In the RT before PBSC mobilization group, patients who required more than 1 LP session to reach the PBSC collection goal after RT had a significantly higher percentage of radiated hematopoietic BM compared to those who required only 1 LP session (mean 9.7% versus 7.2%, P = .002). Overall, our study indicates a negative impact of RT on PBSC mobilization and collection. Apart from emergency settings, it might be beneficial to postpone RT to a post-PBSC collection time point. © 2021 American Society for Blood and Marrow Transplantation. Published by Elsevier Inc. All rights reserved.